Polyamines in mammalian pathophysiology - Sánchez-Jiménez, Francisca; Medina, Miguel Ángel; Villalobos-Rueda, Lorena; Urdiales, José Luis (Cellular and molecular life sciences : CMLS, 2019)
Polyamines (PAs) are essential organic polycations for cell viability along the whole phylogenetic scale. In mammals, they are involved in the most important physiological processes: cell proliferation and viability, nutrition, fertility, as well as nervous and immune systems. Consequently, altered polyamine metabolism is involved in a series of pathologies. Due to their pathophysiological importance, PA metabolism has evolved to be a very robust metabolic module, interconnected with the other essential metabolic modules for gene expression and cell proliferation/differentiation. Two different PA sources exist for animals: PA coming from diet and endogenous synthesis. In the first section of this work, the molecular characteristics of PAs are presented as determinant of their roles in living organisms. In a second section, the metabolic specificities of mammalian PA metabolism are reviewed, as well as some obscure aspects on it. This second section includes information on mammalian cell/tissue-dependent PA-related gene expression and information on crosstalk with the other mammalian metabolic modules. The third section presents a synthesis of the physiological processes described as modulated by PAs in humans and/or experimental animal models, the molecular bases of these regulatory mechanisms known so far, as well as the most important gaps of information, which explain why knowledge around the specific roles of PAs in human physiology is still considered a “mysterious” subject. In spite of its robustness, PA metabolism can be altered under different exogenous and/or endogenous circumstances so leading to the loss of homeostasis and, therefore, to the promotion of a pathology. The available information will be summarized in the fourth section of this review. The different sections of this review also point out the lesser-known aspects of the topic. Finally, future prospects to advance on these still obscure gaps of knowledge on the roles on PAs on human physiopathology are discussed.